Deep commitments: the past, present, and future of religious liberty - Burrus, Trevor; McDonald, David (Cato Institute, 2017)
Introduction : the cleansing fire of religious liberty / Trevor Burrus -- Opening essay : protecting religious liberty in the culture wars / Douglas Laycock -- The opening argument : church, state, and the birth of liberty / John M. Barry -- Religious liberty and the human good / Robert P. George -- As government expands, so should religious liberty protections / Doug Bandow -- Panel discussion I / moderated by Trevor Burrus -- Religious liberty in education / Charles L. Glenn -- Religion, diversity, and the failure of education / Jonathan Zimmerman -- From battleground to common ground : religious liberty in public schools / Charles C. Haynes -- Public schooling and religious equality cannot coexist / Neal McCluskey -- Panel discussion II / moderated by Jason Russell -- Can a surfeit of statutes "accommodate" religious liberty? / Roger Pilon -- The dangers of public accommodation laws to a pluralistic society / Mark L. Rienzi -- Religious exemptions from public accommodations : what's the harm? / Louise Melling -- Panel discussion III / moderated by Ilya Shapiro -- Concluding essay : religious liberty and religious judges / Hon. William H. Pryor, Jr. -- Final thoughts / Ilya Shapiro